2000
DOI: 10.1034/j.1600-0420.2000.078001026.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of near‐work on development of myopia among university students. A three‐year longitudinal study among engineering students in Norway

Abstract: ABSTRACT.Purpose: The aim of this study was to investigate the effect of near-work on development and progression of myopia among adults exposed to high educational demands. Methods: A three-year longitudinal refraction study was performed among 224 Norwegian engineering students (mean age 20.6 years, 117 females and 107 males) measuring their refraction at the beginning and the end of the period. The examinations included automated and clinical refraction in cycloplegia and a questionnaire regarding time spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 13 publications
(21 reference statements)
5
85
3
3
Order By: Relevance
“…3,4 Perhaps the most evident manifestation of ocular pliability throughout life is the development of myopia that is increasingly found to occur in adults. [5][6][7][8] This is most likely to be attributable to accommodative effort but may also involve a second growth spurt in adult life. 5 Accommodation is not the only factor that may influence the shape and size of the globe in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Perhaps the most evident manifestation of ocular pliability throughout life is the development of myopia that is increasingly found to occur in adults. [5][6][7][8] This is most likely to be attributable to accommodative effort but may also involve a second growth spurt in adult life. 5 Accommodation is not the only factor that may influence the shape and size of the globe in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence that myopia can develop and progress in adults, particularly in certain populations (e.g. university students and microscopists) (McBrien & Adams, 1997;Kinge et al, 2000). Myopia is considered to be a major public health concern, due to its increasing prevalence in recent decades and the documented association between myopia and sight-threatening ocular complications such as cataract, retinal detachment, retinal degeneration, and glaucoma (Flitcroft, 2012;Morgan et al, 2012).…”
Section: Human Myopiamentioning
confidence: 99%
“…Studies of myopia in adults have reported incidence levels of myopia ranging from 6% to 22.5% per year and progression rates from -0.13 D/year to -0.24 D/year (Shulkin & Bari, 1986;Zadnik & Mutti, 1987;Lin et al, 1996;Kinge & Midelfart, 1999;Kinge et al, 2000;Onal et al, 2007;Jacobsen et al, 2008). Adultonset myopia also typically occurs due to axial elongation of the eye, with reported rates of axial elongation in young adults ranging from 0.010 to 0.083 mm per year.…”
mentioning
confidence: 99%
See 2 more Smart Citations